Methodological Profiles of the Information Society Studies: New Wine, Old Wineskins? - Šaulauskas, Marius Povilas (Problemos, 2000)
The article explores the methodological underpinnings of the new emerging field of information society studies from a vantage point of the traditional social theory in retrospect. It presents twofold - de dicto and de re - typology of information society theories. First, according to consistently de dicto analysis, focused on the whole set of methodological attitudes employed in information society theories, these are classified in terms of four mainstream paradigms: conflict (a la mode de Marx), functional (a la mode de Durkheim), understanding (a la mode de Weber), and eclectic (a la mode de Tilly). Second, according to de re investigation of the presupposed type of social change itself, the theories in question are clustered around two basic methodological approaches towards the evolution of information society in economic and socio cultural terms of continuation (a la mode de Callinicos and, resp., Giddens) and/or innovation (a la mode de Machlup and, resp., Castells) of manifold societal alterations. It is argued that, taken as a whole, even the most radical information society theories, insisting on the post-modern “Age of Information”, pour old wine (i.e., traditional assembly of methodological instrumentation, devised to tackle with explicitly modem societal change) into new wineskins (i.e., new previously unseen societal morphology ex definition requiring equally unique conceptual apparatus). The article concludes with implications for future research and practice.
Keywords: sociology; methodology; information society; modern sociological theories